Patient Registry and Outcomes for Breast Implants and Anaplastic Large Cell Lymphoma Etiology and Epidemiology (PROFILE): Initial Report of Findings, 2012–2018. (March 2019) - McCarthy, Colleen M.; Loyo-Berríos, Nilsa; Qureshi, Ali A.; Mullen, Erin; Gordillo, Gayle; Pusic, Andrea L.; Ashar, Binita S.; Sommers, Katie; Clemens, Mark W.
Abstract : Background: In January of 2011, the US Food and Drug Administration released a safety communication regarding the potential association between breast implants and anaplastic large cell lymphoma (ALCL). In August of 2012, the American Society of Plastic Surgeons, The Plastic Surgery Foundation, and the Food and Drug Administration signed a cooperative research and development agreement to develop a patient registry entitled the "Patient Registry and Outcomes for Breast Implants and Anaplastic Large Cell Lymphoma Etiology and Epidemiology" (PROFILE). Methods: The first report of the registry findings is presented here. Results: From August of 2012 to March of 2018, a total of 186 distinct cases of breast implant–associated ALCL (BIA-ALCL) in the United States were reported to PROFILE. At the time of this present analysis, complete detailed case report forms have been received for 89 (48%) cases. Median time from implantation of any device to BIA-ALCL diagnosis was 11.0 years (range = 2–44 years; n = 89). At the time of presentation, 96% of cases had local symptoms and 9% had concurrent systemic symptoms. The most common local symptom was a periprosthetic fluid collection seen in 86% of patients. All patients had a history of a textured device; there were no patients who had a smooth-only device history. At the time of initial case report submission, 3 deaths were reported. Conclusions: The PROFILE Registry has shown to be an essential tool in unifying the collection of data pertaining to BIA-ALCL. These data have broadened our understanding of the disease and emphasize the critical importance of detailed tracking of BIA-ALCL cases.